4x+(-3)=-11

Simple and best practice solution for 4x+(-3)=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+(-3)=-11 equation:


Simplifying
4x + (-3) = -11
4x + -3 = -11

Reorder the terms:
-3 + 4x = -11

Solving
-3 + 4x = -11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 4x = -11 + 3

Combine like terms: -3 + 3 = 0
0 + 4x = -11 + 3
4x = -11 + 3

Combine like terms: -11 + 3 = -8
4x = -8

Divide each side by '4'.
x = -2

Simplifying
x = -2

See similar equations:

| -8v=7/3 | | 50=5x+y | | f=9/5c-32 | | 4x+8[x-3]=-4+8x | | 12c^2+19c-21=0 | | 22-3x-4=x/4 | | x(2)=30-13x | | -3+6+5a=7a-8a | | 5x+4(-6x+17)=-65 | | 5/2x+31/2x+15 | | 26-13a=13a-26 | | -5(t^2-2t-10)=0 | | 40-8n=-8[2n+1] | | 4(x+1)3(x-3)=2 | | -14=7x/6 | | x/6-2.3=-21.5 | | 4x^2+10x=16 | | -7x+4-3x=-76 | | x/6-2.3=21.5 | | 6x-3y=16 | | y/4=y/3-3 | | (1/6)(6t-7)=(t+7)/12 | | 2(6d+3)=18-3(-3d+16) | | 2(3x-3)=3(2x+4) | | y-5=5 | | 13w=-13w | | 6v+3/5=-2/5v-1/2 | | 2x+9-4(x+1)=5x+8 | | 90-8x+20= | | 50-4n= | | Z^2+36=-16 | | 0.19y+0.08(y+2000)=1510 |

Equations solver categories